Innovation in Vertical Agriculture in Dutch Cities: Sustainable Solutions with Modern Hydroponics - Loso Judijanto; Nong Chai; Ian Tubangsa (Yayasan Adra Karima Hubbi, 2024)
Vertical agriculture has emerged as an innovative solution to the challenge of food security in densely populated urban areas such as those in the Netherlands. The background of this research is driven by the need to find more efficient and sustainable agricultural methods amid the limitations of conventional agricultural land. The purpose of this study is to examine the potential application of modern hydroponic technology in vertical farming systems in urban Netherlands, as well as to analyze its impact on environmental and economic sustainability. This study uses a qualitative method with a case study approach, where data is collected through interviews with agricultural experts, literature analysis, and direct observation on vertical farming facilities using hydroponic technology. The results show that vertical farming systems with hydroponic technology are able to reduce water use by up to 90% compared to traditional agriculture, as well as increase crop production up to 3 times on the same land area. In conclusion, hydroponic vertical agriculture innovations not only provide solutions to urban land limitations, but also support more environmentally friendly and sustainable agricultural practices. However, challenges in terms of initial costs and technology are still the main obstacles that need to be overcome for wider implementation.